Effect of zero magnetic field on cardiovascular system and microcirculation. (February 2016) - Gurfinkel, Yu.I.; At'kov, O.Yu.; Vasin, A.L.; Breus, T.K.; Sasonko, M.L.; Pishchalnikov, R.Yu.
Abstract: The effects of zero magnetic field conditions on cardiovascular system of healthy adults have been studied. In order to generate zero magnetic field, the facility for magnetic fields modeling "ARFA" has been used. Parameters of the capillary blood flow, blood pressure, and the electrocardiogram (ECG) monitoring were measured during the study. All subjects were tested twice: in zero magnetic field and, for comparison, in sham condition. The obtained results during 60 minutes of zero magnetic field exposure demonstrate a clear effect on cardiovascular system and microcirculation. The results of our experiments can be used in studies of long-term stay in hypo-magnetic conditions during interplanetary missions. Highlights: Exposure of humans in hypomagnetic conditions in spatial facility. Zero magnetic field effects on human's cardiovascular system. Capillary blood velocity enlarged by 17% during zero magnetic field exposure. Cardio intervals increased by 88.7% during zero magnetic field exposure.